Collecting yam (Dioscorea spp.) and sweet potato (Ipomoea batatas) germplasm in traditional agriculture amall-holdigs in the Vale do Ribeira, Sao Paulo, Brazil - Andrade Breáan, E.=700 1 Veaáey, E.A.
(Es, En, Fr)